Liquid Neural Networks - Classification and Time Series Forecasting Use Case - Kavakli, Mehmet; Ucar, Ferhat (Institute of Electrical and Electronics Engineers Inc., 2024)
This study aims to comprehensively examine the potential of Liquid Neural Networks (LNNs) in machine learning field and various application areas. LNNs offer significant advantages over traditional neural networks due to their adaptive learning capacity and dynamic structures. The study involves visual classification using the MNIST dataset and time series analysis on the Yahoo Finance dataset. The performance of the LNN model on these two different datasets has been thoroughly evaluated through the training and testing processes, with results rigorously analyzed. This comprehensive analysis aims to provide an important discussion of the potential uses and advantages of the LNN model. © 2024 IEEE.
Sivi Sinir Aglari ile Siniflama ve Zaman Serisi Tahmini Kullanim rnegi
8th International Artificial Intelligence and Data Processing Symposium, IDAP 2024 -- 21 September 2024 through 22 September 2024 -- Malatya -- 203423
Keywords: Artificial Intelligence; Liquid Neural Networks; MNIST; Model Training; Time Series Forecasting